Executive functions and borderline personality features in adolescents with major depressive disorder - Albermann, Mona; Emery, Sophie; Baumgartner, Noemi; Strumberger, Michael; Erb, Suzanne; Wöckel, Lars; Müller-Knapp, Ulrich; Rhiner, Bruno; Contin-Waldvogel, Brigitte; Bachmann, Silke; Schmeck, Klaus; Berger, Gregor; et al. (Frontiers in Human Neuroscience, 2023)
Background: Executive functions (EF) consolidate during adolescence and are impaired in various emerging psychiatric disorders, such as pediatric Major Depressive Disorder (pMDD) and Borderline Personality Disorder. Previous studies point to a marked heterogeneity of deficits in EF in pMDD. We examined the hypothesis that deficits in EF in adolescents with pMDD might be related to comorbid Borderline Personality features (BPF). Methods: We examined a sample of 144 adolescents (15.86 ± 1.32) diagnosed with pMDD. Parents rated their child’s EF in everyday life with the Behavior Rating Inventory of Executive Function (BRIEF) and BPF with the Impulsivity and Emotion Dysregulation Scale (IED-27). The adolescents completed equivalent self-rating measures. Self- and parent-ratings of the BRIEF scores were compared with paired t-Tests. Correlation and parallel mediation analyses, ICC, and multiple regression analyses were used to assess symptom overlap, parent-child agreement, and the influence of depression severity. Results: Over the whole sample, none of the self- or parent-rated BRIEF scales reached a mean score above T>65, which would indicate clinically impaired functioning. Adolescents tended to report higher impairment in EF than their parents. Depression severity was the strongest predictor for BPF scores, with Emotional Control predicting parent-rated BPF and Inhibit predicting self-rated BPF. Furthermore, the Behavioral Regulation Index, which includes EF closely related to behavioral control, significantly mediated the relationship between depression severity and IED-27 factors emotional dysregulation and relationship difficulties but not non-suicidal self-injuries. Conclusion: On average, adolescents with depression show only subtle deficits in executive functioning. However, increased EF deficits are associated with the occurrence of comorbid borderline personality features, contributing to a more severe overall psychopathology. Therefore, training of executive functioning might have a positive effect on psychosocial functioning in severely depressed adolescents, as it might also improve comorbid BPF. Clinical Trial Registration: www.ClinicalTrials.gov, identifier NCT03167307